Dark Tourism in the land of Sunshine: An intercultural business model for the routes of death and disaster in Portugal - Rodrigues, Ana Cristina Resende (2021)
The main goal of this dissertation is the creation and subsequent implementation of dark tourism routes in Portugal, following a business model that already exists in other cultures. This typology of tourism is an extension of cultural tourism and is classified by the search for places where once disasters, suffering and death occurred. Thus, concentration camps, inactive prisons, serial killers' homes, cemeteries, and all other places that fit into the patterns of death, tragedy and suffering can be considered dark tourism sites. In Portugal, there are some places associated with the practice of dark tourism, although this type of business is not yet sufficiently explored. Therefore, this dissertation intends to use the country’s heritage, which is one of the levers for promoting tourism and an important factor of development, thus justifying the elaboration of a conceptual map associated with tourism. With the delineation of routes in this dissertation, we intend not only to introduce this market niche in the country, but also to contribute innovatively to the tourist dynamics, in order to blur the existing seasonality, which arises from the demand for sun and sea tourism. With the conception and design of these routes, we intend to make a pioneering contribution to the creation of a platform to promote dark tourism in the country. The creation of a business model and a marketing plan results from the need to assess the viability of the implementation of this project, and to discuss the best strategies for implementing it.